Photoluminescence and nonlinear optical phenomena in plasmonic random media - A review of recent works - De Araújo, Cid B.; Kassab, Luciana R.P.; Tolentino Dominguez, C.; Ribeiro, Sidney J.L. [UNESP]; Gomes, Anderson S.L.; Reyna, Albert S. (Elsevier, 2016)
Photoluminescence properties and nonlinear optical response of metal-dielectric nanocomposites (MDNCs) - germanate glasses, bio-cellulose membranes and colloids containing either silver (Ag) or gold (Au) nanoparticles (NPs) - are reviewed. The phenomena discussed are: i. the photoluminescence enhancement observed from rare-earth doped PbO-GeO2 glass containing Ag NPs; ii. optical amplification at 1530 nm in RIB waveguides made with PbO-GeO2 thin films covered with Au NPs; iii. Random Laser emission from a bio-cellulose membrane infiltrated with Rhodamine 6G and containing Ag NPs; iv. the nonlinearity management of high-order processes in colloids containing Ag NPs suspended in acetone. In all discussed cases the influence of the metallic NPs is clearly demonstrated and a procedure to control the nonlinear propagation of light beams in heterogeneous media is presented.
Keywords: Metallic nanoparticles; Nonlinear optics; Photoluminescence; Rare-earth ions